The Effect of Think Pair Share (TPS) to Improve Speaking Ability of Grade VII Students in Junior High School - Heppy Theresia Sitompul; Yanti Kristina Sinaga; Mungkap Mangapul Siahaan (JURNAL PENDIDIKAN BAHASA, 2025)
Mastery of English-speaking skills is crucial in today’s globalized era, yet many students face challenges in achieving fluency. This research is used to find out the effect of the Think-Pair-Share (TPS) learning model on the speaking ability of seventh-grade students at SMP Negeri 1 Siantar. Grounded in Brown's (2004) theory of speaking, which highlights fluency, grammar, comprehension, pronunciation, and vocabulary, and Lyman's (1985) TPS framework, the study emphasizes cooperative learning through structured interaction. A quasi-experimental design with a quantitative approach was employed, involving an experimental class using the TPS model and a control class with conventional teaching. Pre-test and post-test data were collected to measure speaking performance. The findings showed a significant improvement in the experimental class, with the average pre-test score rising from 44.0 to 75.2, compared to the control class's increase from 40.8 to 68.53. The results confirm the TPS model's effectiveness in enhancing students' English-speaking skills. In conclusion, the Think-Pair-Share learning model is a proven instructional method for improving English-speaking skills in junior high school students, contributing to evidence supporting cooperative learning models in language education.